A fluid dynamics perspective on material selection in microbial fuel cell-based biosensors. (15th February 2019) - Quaglio, Marzia; Massaglia, Giulia; Vasile, Nicolò; Margaria, Valentina; Chiodoni, Angelica; Salvador, Gian Paolo; Marasso, Simone Luigi; Cocuzza, Matteo; Saracco, Guido; Pirri, Fabrizio C.
Abstract: This work proposes a novel approach to investigate the behavior of single chamber microbial fuel cells (SCMFCs) based sensors by implementing fluid dynamic simulations to especially investigate the role of diffusion phenomena. When different flow rates are applied (i.e., 25 mL/h and 100 mL/h) the electrolyte flows differently into the cell, changing its speed and the drift-area (Adrift ) in which the fluid/electrolyte is directly pushed during the drift process. Asymmetric squared SCMFCs (a-SCMFCs) ensure optimal fluid motion thanks to their architecture that maximizes the drift-area. In this work a-SCMFCs are tested as acetate bio-sensors using carbon paper and carbon felt as anodes. Experimental results show that the behavior of a-SCMFCs-based sodium acetate biosensors is strongly influenced by the morphology of both carbon felt and carbon paper-based anodes. We used fluid dynamics simulations implementing both the drift and the diffusion processes to gain new information on the behavior of carbon paper and carbon felt anodes. We especially investigated the role of their porosity, in determining the actual fluid distribution and analyte concentration inside the device, at the surface of the porous material and into its volume. We demonstrate that less porous materials, as carbon paper, are more adequate to be used in single chamber MFC-based biosensors. Indeed they can favor an optimal fluid motion, especially favoring more uniform diffusion phenomena and interaction between biofilm and surface than corrugates surfaces, as those characterizing carbon felt, resulting in a more effective analyte conversion and signal transduction. Highlights: Fluid dynamics modelling is an effective tool to design MFC-based biosensors and investigate their behavior. Morphology of materials selected as anodes in SCMFC-based sensors significantly affect the behavior of the systems. The Biofilm/Electrode interface plays a dominant role in SCMFC-based biosensors.